SWIMMER SHOULDER PADA PERENANG GAYA BEBAS - Muhammad Amru Hammam Hammam; Sayyid Sabil Pasha; Nadhifa Azzahra; Erica Kholinne (Jurnal Akta Trimedika, 2024)
Swimmer's shoulder is an overuse injury commonly seen in individuals involved in competitive swimming or repetitive shoulder activities. This condition characterized by pain and dysfunction in the shoulder region, this condition primarily arises from repetitive overhead motions and high-intensity training associated with swimming. Shoulder impingement is identified as the leading cause, with a prevalence of 84%, followed by scapular dyskinesis (82%), and supraspinatus tendinopathy related to overuse (69%). Swimmer shoulder diagnosis is often based on clinical evaluation, patient history, and imaging studies, with an emphasis on identifying specific causative factors and assessing the extent of structural damage. Treatment strategies include a combination of rest, physical therapy, and modifications to training regimens to address muscle imbalances and improve technique. In severe cases, surgical intervention may be considered to repair damaged structures and alleviate persistent symptoms. Preventive measures focus on proper technique, gradual increases in training intensity, and regular strength and flexibility exercises to reduce the risk of swimmer's shoulder. This journal aims to provide a comprehensive overview of the characteristics and biomechanics of proper and improper freestyle strokes, which have a high prevalence in swimmer's shoulder, as well as effective preventive and therapeutic strategies to minimize injury risk. Further research is also needed to evaluate the effectiveness of individualized rehabilitation programs based on the severity of the injury and swimming biomechanics.